The roadmap in selecting a supervisor for Cambodian graduate students in health sciences - Sok, Phan; Sin, Chea (American Journal of Education and Learning, 2024)
With a remarkable increase in the number of students pursuing higher education in Cambodia over the past decade, this article aims to provide practical tips for Cambodian students pursuing a master’s or doctoral degree in health sciences on how to select a supervisor. Unstructured literature searches were conducted, and key factors are outlined to consider when selecting a supervisor, including research interests, statistical expertise, scholarly publication record, mentorship, financial support, expectations, and decision making. Each of these aspects is discussed to help students weigh the relative merits of a potential supervisor. This study is the first ever attempt to outline supervision for graduate students in Cambodia. This article concludes that selecting a potential supervisor for Cambodian graduates in health sciences is necessary to assist them due to the growing number of Cambodian students in higher education, which necessitates the implementation of a well-designed advising mechanism to meet their needs. Further research needs to explore the role of the supervisor, challenges, and needs among Cambodian graduate students as the country continues to grow in graduate education with limited experience and overall resources.